1999
DOI: 10.1006/cbir.1999.0480
|View full text |Cite
|
Sign up to set email alerts
|

ROTOKINESIS, A NOVEL PHENOMENON OF CELL LOCOMOTION‐ASSISTED CYTOKINESIS IN THE CILIATE TETRAHYMENA THERMOPHILA

Abstract: The mechanism responsible for final cell separation at the end of cytokinesis is currently unknown. Knockout strains of the ciliate, Tetrahymena thermophila lacking the kinesin-II homologous molecular motors, Kin1p and Kin2p are paralyzed due to their complete loss of cilia and undergo frequent cytokinesis failures. Observations of live dividing cells revealed that cleavage furrow ingression is normal in kinesin-II double knockout cells until the final stage of cell separation (Brown et al., 1999). During clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 29 publications
3
43
0
Order By: Relevance
“…Hence, the pulling and rotational forces provided by flagellar beating may provide a convenient way to drive the final steps of cell separation which, in trypanosomes, occurs in the absence of any detectable contractile ring. A similar phenomenon, termed rotokinesis, has been observed in Tetrahymena (Brown et al, 1999). Therefore, in addition to its role as a spatial and directional cue for directing cleavage furrow formation, the flagellum plays an active role in cell division in procyclic T. brucei cells.…”
Section: Flagellar Motility and Cytokinesismentioning
confidence: 60%
“…Hence, the pulling and rotational forces provided by flagellar beating may provide a convenient way to drive the final steps of cell separation which, in trypanosomes, occurs in the absence of any detectable contractile ring. A similar phenomenon, termed rotokinesis, has been observed in Tetrahymena (Brown et al, 1999). Therefore, in addition to its role as a spatial and directional cue for directing cleavage furrow formation, the flagellum plays an active role in cell division in procyclic T. brucei cells.…”
Section: Flagellar Motility and Cytokinesismentioning
confidence: 60%
“…As a result, movement of these two flagella, in addition to the twisted motility imposed by the flagellum disposition around the cell body (Hill, 2003), exerts tension on the mid-body and contributes to completion of cell separation. Other modes of movement participate to this process in the ciliate Tetrahymena and in the slime mould Dictyostelium, where the shearing force is provided by complex cilia beating (Brown et al, 1999) and amoeboid movement (Tuxworth et al, 1997), respectively. In all three cases, cells can re-enter the normal cell cycle, progress through mitosis and, therefore, end up multi-nucleated -indicated by the absence of a checkpoint on that final stage of cell division.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that the shaking effect is because of some aspect of the increased aeration during shaking. In addition, it has been reported that Tetrahymena participate in rotokinesis, a mechanism of cell division characterized by coordinated locomotion of daughter cells at the final stage of cytokinesis (Brown et al, 1999). It is possible that a ciliary waveform defect may influence the efficiency of this process and result in slower rates of cell division.…”
Section: Discussionmentioning
confidence: 99%